HINGE MOMENT AND CONTROL FORCE PREDICTION OF EXTRA-300 AEROBATIC AIRCRAFT - Nurohman, Chandra
Aircraft pitch, yaw, and roll controls are controlled by elevator, rudder, and ailerons respectively. Every change in angle of attack and deflection of the surface will change the load on them. There will be a moment generated on their hinge which is transferred to the pilot through linkage system. The pilot need to be able to counter the moment using the stick or wheel devices with some control force. The magnitude of the control force depends on airspeed, altitude, surface geometry, gearing ratio, and hinge moment coefficient. Hinge moment is important to be analyzed since it is the main parameter to check whether an aircraft design comply with regulations, to choose a well-sized actuator for control, and to apply control force cueing in flight simulator. This work is supported by PT T&E Simulation, a simulator company based in Bandung. This work is a part of upgrading program of an aerobatic aircraft simulator in the company. The aircraft discussed in this work is Extra-300 aerobatic aircraft produced by Extra Flugzeugproduktions. Germany. This work presents the development of a tool that is applicable to predict hinge moment coefficients of a conventional subsonic aircraft, along with the validation, and its application to predict hinge moment coefficient of the Extra-300. The obtained hinge moment coefficients are used to predict the stick forces of the aircraft during several aerobatic maneuvers i.e. inside loop, split-s, half cuban 8, and aileron roll maneuver. The maximum longitudinal stick force is 566.97 N occurs in inside loop maneuver and maximum lateral stick force is 340.82 N in aileron roll maneuver. Furthermore, the validation of the hinge moment prediction method is performed using Cessna 172 data. The predicted hinge moment coefficients for this case differs by 3.99% as the lowest happen for elevator’s Chd up to 55% as the maximum happen for aileron’s Cha in which the value will not affect the control force calculation.